(untitled) (Revista de Estudos da Linguagem, 2024)
The ICAO Language Proficiency Rating Scale offers parameters for aeronautical English teaching and assessment focused on oral skills. It assists governments worldwide in assessing pilots and air traffic controllers’ English proficiency, licensing them for international operations. This paper addresses two of the six linguistic areas listed in the Rating Scale, namely fluency and interaction, to understand what conversational elements are present in pilot-controller communications with a view to informing pedagogical material. The analysis is based on a corpus of pilot-controller radio communications in abnormal situations, revealing a more spontaneous code as opposed to the documented Standard Phraseology mandated for routine situations. Corpus Linguistics is the methodology chosen for this investigation, concentrated on the top frequent three-word clusters extracted from the corpus. Investigation of these clusters reveals that fluency and interaction are interconnected and should be considered in a broader perspective that takes into account language in use. To illustrate, ‘we’d like’ and ‘if you can’ are commonly employed as requests in this specific register. The paper concludes by suggesting that learners’ awareness of pragmatic aspects of language is pivotal in the aviation English classroom.